Agreement between the biometric measurements used to calculate the size of the implantable collamer lenses measured with four different technologies - Jorge A Calvo-Sanz; Francisco Poyales; Ying Zhou; Alfonso Arias-Puente; Nuria Garzón (Indian Journal of Ophthalmology, 2022)
Purpose: To evaluate the agreement between the biometric measurements used to calculate the size of the implantable collamer lenses (ICL) with different technologies: swept-source optical coherence tomography, spectral domain optical coherence tomography, and Scheimpflug tomography. Methods: This retrospective observational study included subjects undergoing refractive surgery with posterior chamber phakic IOL implantation to correct their myopia. The anterior chamber depth (ACD) and the horizontal white to white (WTW) or the angle to angle (ATA) distance were measured with the following four devices: the IOLMaster 700 biometer (Carl Zeiss Meditec, Jena, Germany), based on swept-source optical coherence tomography; the Cirrus and Visante optical coherence tomographs (Carl Zeiss Meditec) based on low-coherence interferometry; and the Pentacam rotating Scheimpflug camera (Oculus, Wetzlar, Germany). Results: In the horizontal corneal diameter measurements, there were statistically significant differences between Pentacam–IOLMaster 700 pair (P < 0.001) and Pentacam–Visante pair (P < 0.001). WTW from CIRRUS showed the lowest correlation when paired with Pentacam and IOLMaster 700 (R2 = 0.452 and 0.385 for Visante and R2 = 0.494 and 0.426 for Cirrus). Regarding the linear correlation of the ACD measurements, all pairs of devices were statistically significant and all of them showed a very good correlation index. Conclusion: There is a good agreement between the different devices under evaluation for ACD measurements. As for WTW, the values measured with the different devices showed large discrepancies with low correlation levels, especially when comparing the tomographs with the other devices under evaluation.